Den biskoplege tilsynspraksisen: ein studie av kva verktøy biskopane i Den norske kyrkja brukar i tilsynet med kyrkjelydane og kva leiingsaktivitet denne praksisen medfører - Sele, Asgeir (Tidsskrift for praktisk teologi, 2020)
This article explores the oversight practice that the bishops of Church of Norway are conducting to the congregations by raising the following issues: What tools do the bishops of Church of Norway use in overseeing the congregations and what leadership activities do their practices entail? To shed light on these issues, distributed leadership is used as a research perspective along with Henry Mintzberg's three leadership levels and six leadership roles. The method involves quantitative analysis of postal records for the bishop, visitation talks by bishops and minutes from parish councils, as well as surveys of all the deans in Norway and church department heads at the diocesan offices. The study shows a picture of a diverse selection of tools used by the bishops in their oversight of the congregations. The use of tools documented throughout the study indicates that the bishops are exercising full leadership through oversight, although an untapped potential is clearly present in the practices identified.